2017
DOI: 10.1080/09540253.2017.1410108
|View full text |Cite
|
Sign up to set email alerts
|

Teacher gender, and expectation of reading achievement in New Zealand elementary school students: essentially a barrier?

Abstract: Boys continue to demonstrate lower average achievement in reading than girls. The influence of teacher gender has been explored among the factors explaining this scenario but with mixed results. Further, although teacher expectations have affected student academic outcomes, and student gender-related stereotypical notions have shaped such expectations, the role of teacher gender within this scenario has been neglected. The current study was conducted with a sample of elementary schools, in New Zealand (a natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 53 publications
3
23
0
1
Order By: Relevance
“…The results revealed that male teachers have lower expectations of their students' (both boys and girls) performance in mathematics than their female colleagues. The same pattern was observed for reading in a more recent study (Watson et al, 2017).…”
Section: The Influence Of Teacher Gender and Experience On Teacher Exsupporting
confidence: 84%
See 1 more Smart Citation
“…The results revealed that male teachers have lower expectations of their students' (both boys and girls) performance in mathematics than their female colleagues. The same pattern was observed for reading in a more recent study (Watson et al, 2017).…”
Section: The Influence Of Teacher Gender and Experience On Teacher Exsupporting
confidence: 84%
“…Male teachers had lower expectations than their female colleagues, regardless of student gender. Similarly Watson et al (2017) showed that male teachers presented lower expectations of both boys and girls than their female colleagues. Considering the findings of the present study, it could be inferred that the gender-related discrepancies between teachers in New Zealand and Chile may be the result of cultural differences between the two countries.…”
Section: Discussionmentioning
confidence: 96%
“…An important mechanism of this transformation seems to be the stereotype threat (e.g., Nguyen and Ryan 2008;Schmader 2002;Shapiro and Williams 2012) and selffulfilling prophecy (e.g., Fiedler et al 2002;Gentrup and Rjosk 2018;Watson et al 2017). The indicated phenomena, together with the regulatory function of students' self-expectations and their self-concept of ability in T/S and H/SS (e.g., Fan 2011; Rudman and Phelan 2010;Szumski and Karwowski 2019) are discussed in more detail in the following sections of this paper.…”
Section: Introductionmentioning
confidence: 95%
“…Teachers at school may encourage male students to learn science more, e.g., by praising them for their correctly conducted physical experiments, whereas female students might be motivated to analyze the beauty of Gabriele Mistral's poetry, according to socially shared schema of technically talented boys and humanistically predisposed girls (Eccles et al 1990;Jussim et al 1996;Watson et al 2017). Similarly, at home, parents who keep their daughters away from screwdrivers or their sons away from dolls may show them how to bake cakes and replace a bicycle hub, respectively (Jacobs et al 2004;Simpkins et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation